Brisk Walking for Elderly Individuals with Hypertension - EL Rahmayati; Upik Rahmi; Rizal Ilbert (Shiraz University of Medical Sciences, 2023)
One of the risk factors for cardiovascular disease is hypertension. According to the 2017 globalburden of disease report, it was indicated that the number of individuals worldwide suffering fromhypertension will have reached 1.56 billion by 2025, indicating a 60% rise in its global prevalence.1Research conducted in various countries has revealed a global rise in the prevalence of hypertension,primarily attributed to such factors as population growth, aging, and changes in behavioral risks.Middle- and low-income countries experienced a significant increase in hypertension prevalence incomparison with high-income countries in recent years.1, 2